2020
DOI: 10.4314/tjpr.v19i6.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icariin and quercetin on high glucose-induced neuronal cell apoptosis

Abstract: Purpose: To study the effects of icariin and quercetin on cell apoptotic changes in neurons induced by elevated glucose condition, and the  mechanism involved. Methods: Neonatal male Sprague Dawley rats (n = 48) weighing 5 – 7 g were used. Neuronal cells were isolated from rat hippocampus and cultured after purification. The cells were randomly assigned to six groups: control, high glucose, icariin, quercetin, serine/threonine-specific protein kinase (Akt) inhibitor, and Akt agonist groups. The Akt inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Epimedium is a plant commonly known as Horny Goat Weed or Yin Yang Huo, used as a tonic agent in Chinese Traditional Medicinal system [22]. Icariin has been reported to possess several pharmacological and biological properties such as antidepressant, J o u r n a l P r e -p r o o f apoptotic, immunomodulating and preventing osteoporosis [23,24]. Extensive literature indicated that Icariin also acts as a potent anticancer agent that can inhibit tumor cell growth and proliferation [25][26][27][28].…”
Section: Structural Elucidation Of the Isolated Compoundsmentioning
confidence: 99%
“…Epimedium is a plant commonly known as Horny Goat Weed or Yin Yang Huo, used as a tonic agent in Chinese Traditional Medicinal system [22]. Icariin has been reported to possess several pharmacological and biological properties such as antidepressant, J o u r n a l P r e -p r o o f apoptotic, immunomodulating and preventing osteoporosis [23,24]. Extensive literature indicated that Icariin also acts as a potent anticancer agent that can inhibit tumor cell growth and proliferation [25][26][27][28].…”
Section: Structural Elucidation Of the Isolated Compoundsmentioning
confidence: 99%